Two new Begonia sect. Baryandra species from the Visayas islands, Philippines revealed by morpho-anatomical and molecular analyses - Bucay, Mark Angelo C.; Tandang, Danilo N.; Tan-Sumagaysay, Jeanette Mara; Hsu, Hao-Chun; Rubite, Rosario R.; Chung, Kuo-Fang (Phytotaxa, 2026)
Two new species of Begonia section Baryandra, both endemic to islands in the Visayas, Philippines are described and illustrated. Begonia camugao from Bohol island and B. matulis from Cebu island were both observed in shaded forest areas with exposed limestone formations, a habitat typically preferred by most Begonia sect. Baryandra species. Morphological characterization of the species shows multiple characters which distinguish these species from their congeners. Phylogenetic placement of the species based on the nuclear ribosomal ITS region (ITS1, ITS2, and 5.8S gene) shows their distinctiveness, nested within a clade of Visayas islands species. Current progress in the knowledge of Begonia species in the Visayas islands is crucial for understanding the diversity of plants in the country, since these areas are blind spots for studies of Begonia diversity. Diagnostic characters of both species and illustrations are provided.